Integrating Digital Wordwall Media In EFL Learning to Improve Student’s Reading Comprehension - Dewi Putri Tuah Susila; Abd. Kamarrudin; Moh. Abraham Akbar Eisenring; Mashuri Mashuri (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This aim of this study is to find whether the use of digital wordwall media can improve reading comprehension of the grade eight students of SMPN 19 PALU. This study used a quantitative approach, using a quasi-experimental design, this type of research design consists of two group namely experimental group and control group. The population of this study consists of all eighth-grade students at SMPN 19 Palu, totaling 110 students. The researcher employed random sampling, with a total sample of 54 student, 24 students from class D as the experimental group and 30 students from class A as the control group. Data collection in this study used tests in the form of pre-tests and post-tests. After analyzing the data, it was found that the average score of students in the experimental class increased from 47.87 in the pre-test to 69.04 in the post-test. In addition, the control class showed an increase in the average score from 46.86 to 55.36 within the same time frame. The results indicated that the t-test value (2.655) exceeded the critical t-value (1.675). The findings support the acceptance of the alternative hypothesis, indicating that the integration of digital wordwall media has a significant positive impact on students’ reading comprehension.